Costa del Sol (Spain), analysis of economic and land changes caused by tourism - Almeida-García, Fernando (My University, 2016)
Malaga is in southern Spain, in a region called Andalusia. Costa del Sol belongs to the province of Malaga, near the Strait of Gibraltar and near the coast of Africa (about 300 km) and about 2,300 km of Sluptz. The Costa del Sol is next to the Mediterranean Sea and near the Atlantic Ocean. Strong and rapid growth of tourism in the countries of southern Europe and in Poland. Spain currently (2015) is the third largest inbound of international tourism (68 mil.) and the second inbound in tourism revenue. Europe is a major world tourist region. The first recipient of tourism in the world is France. Most tourism takes place between developed countries.
Costa del Sol (España). Análisis de cambios económicos y territoriales provocados por el turismo
Keywords: Turismo - Costa del Sol; Impactos turísticos; Cambios territoriales